Establishment and validation of a method for determining anti-Xa factor potency of enoxaparin sodium - En Zhang; Hanyan Zou; Yandong Dong; Bing Liu; Xiaorong Yang (PeerJ)
This study successfully established and validated an efficient, reliable, and user-friendly method for determining the anti-Xa factor potency of enoxaparin sodium. Comprehensive validation experiments demonstrated the method’s excellent performance in terms of specificity, linearity, precision, accuracy, and robustness. The method exhibited a linear detection range of 0.054–0.192 IU/mL with a strong correlation coefficient, and its precision, robustness, and consistency with the European Pharmacopoeia method were all within 2.0% relative standard deviation (RSD). These results indicate high reproducibility and strong applicability, making the method suitable for seamless transfer between laboratories. Accuracy experiments revealed recovery rates ranging from 98.0% to 102.0%, confirming the reliability of the results. The validation design and performance of this method comply with the requirements of ICH guidelines and the Chinese Pharmacopoeia. Compared with traditional methods, this approach significantly reduces sample and reagent consumption, lowers experimental costs, and optimizes operational procedures, offering a low-cost, high-efficiency tool for quality control. These findings provide essential technical support for the production and quality monitoring of enoxaparin sodium and serve as valuable references for the development and validation of quality standards for similar biological products.